Creating Nation Brand: The Model of Qatar - Nawaf Al-Tamimi (17902240) (2023)
In this chapter, the authors argue that Qatar established its nation brand by simultaneously improving different qualities needed for creating a nation brand. In so doing, the chapter presents information about different aspects of Qatari nation brand and Qatar’s political activities. Also, different aspects of nation branding such as Qatar’s economic profile, different humanitarian activities performed by Qatar, and this state’s endeavors to promote sport and tourism in the country are described in detail in this chapter. Other Information Published in: Qatar’s Nation Branding and Soft Power : Exploring the Effects on National Identity and International Stance License: http://creativecommons.org/licenses/by/4.0/ See chapter on publisher's website: http://dx.doi.org/10.1007/978-3-031-24651-7_4 Additional institutions affiliated with: School of Psychology and Social Work - DI